The Wheat Intrinsically Disordered Protein TdRL1 Negatively Regulates the Type One Protein Phosphatase TdPP1 - Fatma Amor; Mariem Bradai; Ikram Zaidi; Vitor Amorim-Silva; Nabil Miled; Moez Hanin; Chantal Ebel (Biomolecules)
Type 1 protein phosphatases (PP1s) are crucial in various plant cellular processes. Their function is controlled by regulators known as PP1-interacting proteins (PIPs), often intrinsically disordered, such as Inhibitor 2 (I2), conserved across kingdoms. The durum wheat TdRL1 acts as a positive regulator of plant stress tolerance, presumably by inhibiting PP1 activity. In this work, co-immunoprecipitation and bimolecular fluorescence complementation (BiFC) assays demonstrate that the durum wheat TdPP1 interacts with both TdRL1 and At-I2 in vivo. YFP fluorescence restored after TdRL1-TdPP1 interaction decorated specifically the microtubular network of the tobacco co-infiltrated cells. In vitro phosphatase assays revealed that TdRL1 inhibited the activity of wild-type TdPP1 and two mutant forms (T243M and H135A) in a concentration-dependent manner, showing a novel and potent inhibition mechanism. Structural modeling of the TdPP1-inhibitor complexes suggested that both At-I2 and TdRL1 bind to TdPP1 by wrapping their flexible C-terminal tails around it, blocking access to the active site. Remarkably, the model showed that TdRL1 differs from At-I2 in its interaction with TdPP1 by trapping the phosphatase with its N-terminal tail. These findings provide important insights into the regulatory mechanisms governing the activity of PP1s in plants and highlight the potential for targeted inhibition to modulate plant stress responses.